Lexical transformation in the translation of cultural terms: A case study of Ayu Utami’s Saman - Mazida Izzatul Azka; Adi Sutrisno (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study investigates the lexical transformations employed in the English translation of cultural terms in Ayu Utami’s Indonesian novel Saman. Focusing on a domain—Indonesian-English literary translation—that remains underexplored, this research analyzes the strategies used to render culture-specific items (CSIs) accessible while preserving their cultural meaning. Employing Newmark’s taxonomy of translation procedures within a qualitative comparative framework, the analysis identified 277 cultural terms. These were categorized as follows: social culture (24.91%); material culture (16.97%); ecology (15.16%); and gestures (9.39%), with the largest category comprising organization, customs, and religion (33.57%). From these, 119 instances of lexical transformation were analyzed. Generalization emerged as the predominant strategy (40.34%), suggesting a primary aim of enhancing reader clarity. This was followed by specification (23.53%), compensation (15.97%), and modulation (12.61%), while metaphorical transformation (4.20%) and differentiation (3.36%) were least frequent. The findings indicate that while lexical transformation is indispensable for cross-cultural meaning transfer, its application—particularly the reliance on generalization—can attenuate cultural specificity. The study underscores the translator's critical role in negotiating between cultural fidelity and target-culture comprehensibility. By elucidating these nuanced decision-making processes, this research contributes to translation studies by delineating culturally oriented strategies specific to Indonesian literature. It ultimately posits that literary translation functions as a complex act of intercultural mediation, significantly influencing the global reception of works like Saman.